2015
DOI: 10.1002/ca.22615
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent intraneural ganglion cysts: Pathoanatomic patterns and treatment implications

Abstract: The etiology of intraneural ganglion cysts has been poorly understood. This has resulted in the development of multiple surgical treatment strategies and a high recurrence rate. We sought to analyze these recurrences in order to provide a pathoanatomic explanation and staging classification for intraneural cyst recurrence. An expanded literature search was performed to identify frequencies and patterns in cases of intraneural ganglion cyst recurrences following primary surgery. Two univariate analyses were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…Utilizing an existing database of all reported cases of intraneural ganglion cysts (Desy et al, ), we identified 80 reports with MR imaging data. Three reports exhibited the complex lobulated subparaneurial pattern—one in the CFN, arising from the anterior aspect of the STFJ (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing an existing database of all reported cases of intraneural ganglion cysts (Desy et al, ), we identified 80 reports with MR imaging data. Three reports exhibited the complex lobulated subparaneurial pattern—one in the CFN, arising from the anterior aspect of the STFJ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A lack of consensus on the mechanism underlying cyst formation and treatment led to suboptimal outcomes and a high recurrence rate. In the past decade, since the unifying articular theory (Spinner et al, ) explained the pathogenesis of these cysts, outcomes have improved and recurrences have decreased (Desy et al, ); in addition the more prevalent use of magnetic resonance imaging (MRI) or ultrasound for diagnosis of peripheral nerve lesions has revealed intraneural ganglion cysts to be more common than previously believed.…”
Section: Introductionmentioning
confidence: 99%
“…4,[5][6][7][12][13][14] We speculate that failure to divide the jointganglion connection could be associated with a high rate of IGC recurrence. [2][3][4][9][10][11]15 The present study comprises an institutional series of IGCs involving the medial plantar nerve treated in various ways. The aim of the current study was to provide further support for the principles underlying the articular theory, and to explain the successes and failures of various treatment options.…”
Section: Resultsmentioning
confidence: 99%
“…There are multiple theories regarding the formation of intraneural ganglion cysts with the articular/synovial theory being most widely accepted. According to this theory, cysts are formed from a capsular defect of an adjacent joint so that synovial fluid spreads along the epineurium of a nerve branch [19]. It is possible for cysts to arise from the proximal tibiofibular joint, to extend over the peroneal nerve to the sciatic nerve, and then to descend into the tibial nerve [7].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive excision can result in nerve damage. Clipping or excision of intraarticular nerve ends can only be performed at specialized centers [19].…”
Section: Discussionmentioning
confidence: 99%